Analyzing Parental Perceptions of Smartphone Usage in Early Childhood: Educational Potential and Risk Management - Yuniarni, Desni; Surjaningrum, Endang R.; Dewi, Triana Kesuma (Universitas Pendidikan Ganesha, 2024)
Smartphone usage has significantly increased across various age groups, including early childhood. This phenomenon presents both concerns and opportunities for parents to utilize technology as a medium for stimulating children’s development. This study aims to explore parents' perceptions of the benefits and negative impacts of smartphone usage for young children and to analyze differences in perceptions based on parents' demographic characteristics. The research employs a descriptive quantitative approach with a comparative analysis. The sampling technique used is stratified random sampling, involving 197 parents of kindergarten children aged 3-6 years as respondents. Data were collected through a Likert-scale questionnaire distributed online via Google Forms. The analysis results indicate that 65% of parents perceive smartphones as beneficial educational tools for supporting children's cognitive development. However, 60% of parents express concerns about the negative impacts of smartphone usage, particularly on children's social-emotional and motor development. The findings also reveal that parents with higher education levels are more focused on controlling smartphone usage risks by setting time limits and content restrictions, while parents with middle-level education tend to emphasize the entertainment benefits of smartphones for children. The study concludes that strict supervision of smartphone usage in early childhood is necessary to minimize negative impacts and maximize its educational benefits.